Porcine epidemic diarrhea virus E protein inhibits type I interferon production through endoplasmic reticulum stress response (ERS)-mediated suppression of antiviral proteins translation. (20th December 2022) - Zheng, Liang; Liu, Hongxian; Tian, Zhipiao; Kay, Matthew; Wang, Hongyu; Wang, Xianhe; Han, Hao; Xia, Wenlong; Zhang, Jiankang; Wang, Wenling; Gao, Zhenqiu; Wu, Zhijun; et al.
Abstract: Porcine epidemic diarrhea virus (PEDV) envelope protein (E) is recognized as a viroporin that plays important functions in virus budding, assembly and virulence. Our previous study found that PEDV E protein induces endoplasmic reticulum stress (ERS), as well as suppresses the type I interferon (IFN) response, but their link and underlying mechanism remain obscure. To better understand this relationship, we investigated the roles of PEDV E protein-induced ERS in regulating cellular type I IFN production. Our results showed that PEDV E protein localized in the ER and triggered ERS through activation of PERK/eIF2α branch, as revealed by the up-regulated phosphorylation of PERK and eIF2α. PEDV E protein also significantly inhibited both poly(I:C)-induced and RIG-I signaling-mediated type I interferon production. The PERK/eIF2α branch of ERS activated by PEDV E protein led to the translation attenuation of RIG-I signaling-associated antiviral proteins, resulting in the suppression of type I IFN production. However, PEDV E protein had no effect on the mRNA transcription of RIG-I-associated molecules. Moreover, suppression of ERS with 4-PBA, a widely used ERS inhibitor, restored the expression of RIG-I-signaling-associated antiviral proteins and mRNA transcription of IFN-β and ISGs genes to their normal levels, suggesting that PEDV E protein blocks the production of type I IFN through inhibiting expression of antiviral proteins caused by ERS-mediated translation attenuation. This study elucidates the mechanism by which PEDV E protein specifically modulates the ERS to inhibit type I IFN production, which will augment our understanding of PEDV E protein-mediated virus evasion of host innate immunity. Highlights: PEDV E protein localizes in ER and triggers ERS through activation of PERK/eIF2α branch. PEDV E protein inhibits both poly(I:C)-induced and RIG-I signaling-mediated type I interferon production. PEDV E protein blocks the production of type I IFN through inhibiting expression of RIG-I-associated antiviral proteins caused by ERS-mediated translation attenuation.